2016
DOI: 10.1371/journal.pone.0162844
|View full text |Cite
|
Sign up to set email alerts
|

Association between Intimate Partner Violence during Pregnancy and Adverse Pregnancy Outcomes in Vietnam: A Prospective Cohort Study

Abstract: BackgroundViolence against pregnant women is an increasing public health concern particularly in low- and middle-income countries. The purpose of this study was to measure the association between intimate partner violence (IPV) during pregnancy and the risk of adverse birth outcomes.MethodsProspective cohort study of 1276 pregnant women in Dong Anh district, Vietnam. Women with gestational age less than 24 weeks were enrolled and interviewed. Repeated interviews were performed at 30–34 weeks gestation to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
66
5
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 30 publications
15
66
5
3
Order By: Relevance
“…Despite the evidence frequently associated with physical violence during pregnancy, this relationship is not a consensus in recent literature. An investigation performed almost two decades ago in Norway did not show a positive correlation, but more recent studies developed in Vietnam (3) , East Timor (25) and the South region of Brazil (26) reported this association. Different methodologies and the level of economic and sociocultural development of the countries where research is performed can contribute to making this association questionable.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Despite the evidence frequently associated with physical violence during pregnancy, this relationship is not a consensus in recent literature. An investigation performed almost two decades ago in Norway did not show a positive correlation, but more recent studies developed in Vietnam (3) , East Timor (25) and the South region of Brazil (26) reported this association. Different methodologies and the level of economic and sociocultural development of the countries where research is performed can contribute to making this association questionable.…”
Section: Discussionmentioning
confidence: 91%
“…In Brazil, a recent prospective cohort study showed a prevalence of 9.3% in the Northeast region and 25.6% (9) in São Paulo (6) . In both periods and in all the studies, the most frequent violence category was the psychological one, followed by physical and sexual (3)(4)(5)(6)(7)(8)(9) . Violence, in all its forms, implies several consequences to maternal and neonatal health.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Forty-one studies (82%, n = 41) were of high methodological quality (indicating low risk of bias) ( Table 2). [18][19][20][21][22][23][24][25][26]28,29,[31][32][33][34][35][36][37][38][39][40][41]43,[46][47][48][49][51][52][53][56][57][58][59][60][61][62][63][65][66][67] Most of the studies with high or moderate risk of bias obtained low scores in sample selection 30,45,50,54,55,64 or comparability. 27,45,50,…”
Section: Methodological Quality Of Studiesmentioning
confidence: 99%
“…Studies have indicated that IPV during pregnancy affects health of women and pregnancy [1012]. Peterson et al conceptualized the effects of IPV to pregnancy and indicated that physical violence may cause direct injury to the gravid uterus leading to adverse pregnancy outcomes [13].…”
Section: Introductionmentioning
confidence: 99%